BERAT POTONG DAN BAGIAN OFFAL EXTERNAL ITIK BALI JANTAN YANG DIBERI PAKAN KOMERSIAL DISUBSTITUSI POLLAR DAN ADITIF ”DUCK MIX” - Agus Putu Wiradhana; Ni Wayan Siti; I Nyoman Tirta Ariana (Animal Science Study Program, Faculty of Animal Husbandry, Udayana University, 2013)
This study to determine the effect of substitution and addition pollard duck mix in the commercial ration, the weight cut and the external offal of ducks Bali age of ten weeks. Ducks fed 100% commercial as treatment A (control), ducks fed commercial pollard 85% + 15% + 0.3% duck mix as treatment B, ducks fed a commercial 70% + 30% + pollard